Food security portal for Africa South of the Sahara - International Food Policy Research Institute (International Food Policy Research Institute, 2021)
The Africa south of the Sahara Food Security Portal presents current information about agriculture, food security, and nutrition in Africa south of the Sahara and about dynamic developments in the region’s food system. It is facilitated by the International Food Research Institute (IFPRI) and brings together a network of regional partners.